Microstructural characterization of alloyed palladium coated copper wire under high temperature. (May 2021) - Eto, Motoki; Araki, Noritoshi; Yamada, Takashi; Sugiyama, Masaaki; Fujimoto, Shinji
Abstract: Palladium coated copper (PCC) wire has been increasingly used in the semiconductor package in the last 10 years, especially in consumer products as a low-cost alternative to gold (Au) bonding wire. However, the PCC wire is still not widely used in the automotive industry due to the reliability limitations under a high temperature condition. In order to improve the long term reliability of PCC wire under a high temperature condition, new additive elements in the Cu core have been considered. In this paper, we investigate the role of additive elements in PCC wire and their effect on corrosion resistance under high temperature conditions. Pd and platinum (Pt) are examined as additive elements. Additive Pd and Pt in PCC wire become a cause of degradation for the stitch bond reliability under the high temperature condition due to the different degradation microstructure from conventional PCC wire. Highlights: Effects of alloying elements in copper wire material Performance of bond reliability under high temperature environment Intergranular corrosion in copper wire material